PENGARUH HARGA, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEBLAK PASTA TAMAN SISWA BAGI MAHASISWA SEKOLAH TINGGI ILMU EKONOMI (STIE) WIDYA WIWAHA YOGYAKARTA (Prosiding dan Call Paper Widya Wiwaha, 2023)
The purpose of this study was to determine the effect of price, product quality, and promotion on purchasing decisions of Seblak Pasta Taman Siswa products. The population in this study are Seblak Pasta Taman Siswa consumers, STIE Widya Wiwaha Yogyakarta students. This research is a quantitative research. The sample in this study was taken as many as 42 respondents with nonprobability sampling technique. The type of data used is primary and secondary data using data collection methods, namely questionnaires. Data analysis techniques are validity test, reliability test, classic assumption test, multiple regression analysis test, T-test, F-test and coefficient of determination test (R2). Based on the results of the t test analysis, it is known that price (X1) has a significant effect on purchasing decisions (Y) supported by t count (2.131) greater than t table 1.30364 with a significance value of 0.040 less than 0.5. (Y). Product quality (X2) has a significant effect on purchasing decisions (Y) supported by the t count (2.051) greater than t table 1.30364 with a significance value of 0.104 less than 0.5. (Y). Promotion (X3) has a significant effect on purchasing decisions (Y) supported by t count (1.665) greater than t table 1.30364 with a significance value of 0.047 less than 0.5 (5%), it can be concluded that the variable price (X1), product quality (X2) and promotion (X3) simultaneously have a positive and significant effect on purchasing decisions (Y). The results of the coefficient of determination show that the effect of the independent variable on the dependent is 0,699 or 66.9% and 33.1% is influenced by other variables outside of this variable.
Keywords: Price; Product Quality; Promotion; Purchase Decision; Seblak Pasta Products